Infectious Pancreatic Necrosis Virus: Lyophilization and Subsequent Stability in Storage at 4 C - Wolf, Ken (1969)
Infectious pancreatic necrosis virus (ATCC strain VR # 299) was lyophilized with different additives and stored at 4 C. Ampoules were assayed at 2 days, at 1, 3, and 6 months, and at 1, 3, and 4 years. Processing losses were least and subsequent maintenance of infectivity was best in skim milk, lactalbumin hydrolysate, and lactose. Quantitative data are given in tabular form.